Immunodominant SARS Coronavirus Epitopes in Humans Elicited both Enhancing and Neutralizing Effects on Infection in Non-human Primates - Wang, Qidi; Zhang, Lianfeng; Kuwahara, Kazuhiko; Li, Li; Liu, Zijie; Li, Taisheng; Zhu, Hua; Liu, Jiangning; Xu, Yanfeng; Xie, Jing; Morioka, Hiroshi; Sakaguchi, Nobuo; et al. (ACS infectious diseases, 2016)
Severe acute respiratory syndrome (SARS) is caused by a coronavirus (SARS-CoV) and has the potential to threaten global public health and socioeconomic stability. Evidence of antibody-dependent enhancement (ADE) of SARS-CoV infection in vitro and in non-human primates clouds the prospects for a safe vaccine. Using antibodies from SARS patients, we identified and characterized SARS-CoV B-cell peptide epitopes with disparate functions. In rhesus macaques, the spike glycoprotein peptides S471–503, S604–625, and S1164–1191 elicited antibodies that efficiently prevented infection in non-human primates. In contrast, peptide S597–603 induced antibodies that enhanced infection both in vitro and in non-human primates by using an epitope sequence-dependent (ESD) mechanism. This peptide exhibited a high level of serological reactivity (64%), which resulted from the additive responses of two tandem epitopes (S597–603 and S604–625) and a long-term human B-cell memory response with antisera from convalescent SARS patients. Thus, peptide-based vaccines against SARS-CoV could be engineered to avoid ADE via elimination of the S597–603 epitope. We provide herein an alternative strategy to prepare a safe and effective vaccine for ADE of viral infection by identifying and eliminating epitope sequence-dependent enhancement of viral infection.